The reality of government communication in hitu lama negeri development planning, Central Maluku Regency - Kaliky, Pahrul Idham; Wance, Marno; Matdoan, Muhammad Yahya (International research journal of management, IT and social sciences, 2020)
This research was to understand the reality of development communication in Hitu Lama Negeri, Central Maluku Regency. The purpose of this research is to determine the communication barriers of the Saniri Negeri and Government institutions in planning the development of the country. The results of the study, it found that obstacles to development planning caused conflicts of national interest, namely (1). Some of the people/residents of Negeri Hitu Lama have experienced a decline in the trust of the head of the existence of the Traditional Institution (Saniri Negeri) so that it hinders development planning. (2) Planning for the development of Hitu Lama Negeri still has conflicts of interest, institutional egos, causing delays in development planning. The development communication pattern used is the local customary approach like the state government carries out personal communication with customary institutions to build harmony in carrying out development planning.